2016
DOI: 10.1002/bem.21985
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1950 MHz W‐CDMA‐like signal on human spermatozoa

Abstract: There are growing concerns about how electromagnetic waves (EMW) emitted from mobile phones affect human spermatozoa. Several experiments have suggested harmful effects of EMW on human sperm quality, motility, velocity, or the deoxyribonucleic acid (DNA) of spermatozoa. In this study, we analyzed the effects on human spermatozoa (sperm motility and kinetic variables) induced by 1 h of exposure to 1950 MHz Wideband Code Division Multiple Access (W-CDMA)-like EMW with specific absorption rates of either 2.0 or 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Ex vivo investigation yielded ambivalent observations and conclusions in a few studies with human sperm on the influence of RF-EMF with respect to oxidative stress and quality, although similar exposure durations (45-90 min) and doses (SAR: 1-6 W/kg) were applied [165][166][167][168]. Two studies reported no signs of increased ROS, no oxidative DNA damage, or any other negative effects such as induced cell death and reduction in sperm quality, when sperm was exposed to a 900 MHz GSM or a 1.95 GHz UMTS signal [166,167]. In contrast, oxidative stress and, in some cases, massive DNA damage and loss of sperm vitality were observed after exposure to 900 MHz GSM or 2.45 GHz WiFi signal [165,168].…”
Section: In Cultured Cellsmentioning
confidence: 99%
“…Ex vivo investigation yielded ambivalent observations and conclusions in a few studies with human sperm on the influence of RF-EMF with respect to oxidative stress and quality, although similar exposure durations (45-90 min) and doses (SAR: 1-6 W/kg) were applied [165][166][167][168]. Two studies reported no signs of increased ROS, no oxidative DNA damage, or any other negative effects such as induced cell death and reduction in sperm quality, when sperm was exposed to a 900 MHz GSM or a 1.95 GHz UMTS signal [166,167]. In contrast, oxidative stress and, in some cases, massive DNA damage and loss of sperm vitality were observed after exposure to 900 MHz GSM or 2.45 GHz WiFi signal [165,168].…”
Section: In Cultured Cellsmentioning
confidence: 99%
“…One such study reported a significant reduction in the sperm motility rate [Mailankot et al, ], while other reports found no significant effects [Dasdag et al, ; Ribeiro et al, ; Imai et al, ; Yildirim et al, ]. In addition, we reported that cellular phone RF‐EMWs have no adverse effects on human spermatozoa [Nakatani‐Enomoto et al, ]. While some investigators have reported effects of cellular phone RF‐EMW exposure on spermatozoa, there are almost no reports of effects on oocytes.…”
Section: Introductionmentioning
confidence: 69%